Estudo comparativo de β-selenoaminas e disselenetos em modelos hepatotóxico e alternativo - Stefanello, Sílvio Terra (2017)
Organic selenium compounds, Ebselen and diphenyl diselenide (DPDS), possess numerous characteristics such as, antioxidant activity, anti-inflammatory among others. In this regard, new molecules have been produced through the insertion of functional groups on the chemical structure of classical selenium compounds, with an intention to produce new drugs. In this study, we verified the pharmacological effects of β-selenoamines or monosselenides 1-phenyl- 3-(p-tolylselanyl)propan-2-amine (C1) and 1-(2-methoxyphenylselanyl)-3-phenylpropan-2- amine (C2) and DPDS and analogs of DPDS 1,2-bis(2-methoxyphenyl)diselenide (C3) and 1,2-bisp-tolyldiselenide (C4). This compounds were tested through experimental assays using Ceanorhabditis elegans (C. elegans) and a model of tioacetamide-induced acute liver damage in mice. The C. elegans exposure of organic selenium compounds at 200 µM keeps the same survival rates and behavior parameters than control group. However, except C1, all compounds reduced the interval of defecation cycle, which was associated with the inhibition of the acetylcholinesterase. The compounds protected the C. elegans against juglone-induced oxidative damage, keeping the survival rates similar than control group. In addition, juglone treatment also induced the expression of GST-4 and only C2 showed protective activity. In the liver damage model, only the treatment with DPDS protected the liver of the necrosis process as well as normalized the transaminases levels. However, all tested compounds at 15.6 mg kg- 1 promoted significant changes in the oxidative stress parameters, which maintain the cellular viability and reduce the edema. Therefore, our results demonstrated that both β-selenoamines and analogs of DPDS presented protective and reversible effects when it is generated by oxidative stress, which characterizes these molecules as being promising antioxidants.